2018
DOI: 10.1016/j.still.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Soil labile organic carbon fractions and soil organic carbon stocks as affected by long-term organic and mineral fertilization regimes in the North China Plain

Abstract: Soil labile organic carbon fractions and soil organic carbon stocks as affected by long-term organic and mineral fertilization regimes in the North ChinaPlain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
152
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 245 publications
(165 citation statements)
references
References 90 publications
10
152
0
3
Order By: Relevance
“…The estimated order in the increase of CO 2 -C evolution after adding organic amendments to soils (artificial soil mixtures; Fig. 1) confirms literature data about the amendment-specific biodegradability in soils (charcoal < farmyard manure < sheep faeces < straw) (Atkinson et al, 2010;Guenet et al, 2010;Grunwald et al, 2016;Hansen et al, 2016;Sarma et al, 2017;Teutscherova et al, 2017;Li et al, 2018a). Aside from mineralization during incubation, the added organic amendments increased the OC content in soils (Tab.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The estimated order in the increase of CO 2 -C evolution after adding organic amendments to soils (artificial soil mixtures; Fig. 1) confirms literature data about the amendment-specific biodegradability in soils (charcoal < farmyard manure < sheep faeces < straw) (Atkinson et al, 2010;Guenet et al, 2010;Grunwald et al, 2016;Hansen et al, 2016;Sarma et al, 2017;Teutscherova et al, 2017;Li et al, 2018a). Aside from mineralization during incubation, the added organic amendments increased the OC content in soils (Tab.…”
Section: Discussionsupporting
confidence: 83%
“…For example, straw as a biodegradable organic amendment is decomposed relatively rapidly by microorganisms which is reflected in high degradation rates (Powlson et al, 2011;Hansen et al, 2016). In contrast, farmyard manure contains both biodegradable and stabilized organic carbon and has longer turnover rates in soil environments (Kö rschens et al, 1994;Haynes and Naidu, 1998;Li et al, 2018a). Another frequently used fertilizer is charcoal, which is characterized by its superior stability in soils compared to other organic amendments (Glaser et al, 2002;Kuzyakov et al, 2009;Li et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rice roots might be the main source of subsoil carbon inputs, and the balance between the accumulation of organic carbon during the season of rice planting and the decomposition of organic carbon caused by the enhanced microbial activity (increase of the MBC content) during the season of garlic planting could be the reason for the slight but insignificant decreases in the TOC of the subsoil (20–100 cm). In contrast, for rice–leafy vegetable rotation land, long‐term rice planting can provide continuous inputs of organic materials and accumulation of organic carbon; however, the excessive application of N fertilizers can significantly affect the abundance and function of soil microorganisms (Li, Wen, et al, ; Qin et al, ), which then causes different changes in TOC and labile fractions compared with rice–garlic rotation land. A recent study found that the MBC content was significantly decreased and the cellulose‐degrading enzymes were reduced by 30–39% under nitrogen enrichment, which finally induced a reduction in soil respiration (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a high LOC content is required for soil quality due to its quick decomposition, whereas a low LOC content is beneficial for carbon sequestration (Chen et al, ; Li, Wen, et al, ). The proportion of LOC to TOC can be used to reflect SOC stability (Li et al, ; Sheng et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation